2017
DOI: 10.1001/jama.2017.4451
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Home Noninvasive Ventilation With Oxygen Therapy vs Oxygen Therapy Alone on Hospital Readmission or Death After an Acute COPD Exacerbation

Abstract: IMPORTANCE Outcomes after exacerbations of chronic obstructive pulmonary disease (COPD) requiring acute noninvasive ventilation (NIV) are poor and there are few treatments to prevent hospital readmission and death.OBJECTIVE To investigate the effect of home NIV plus oxygen on time to readmission or death in patients with persistent hypercapnia after an acute COPD exacerbation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
557
2
25

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 508 publications
(603 citation statements)
references
References 33 publications
19
557
2
25
Order By: Relevance
“…Results showed that adding home NIV to oxygen therapy significantly prolonged the time to readmission or death within 12 months. 267 Two previous retrospective studies 268,269 and two of three RCTs 267,270-273 reported reductions in re-hospitalization and improved survival with using NPPV post-hospitalization. Two studies reported decreases in mortality and hospitalization rates while another showed no benefit of NPPV for survival.…”
Section: Ventilatory Supportmentioning
confidence: 97%
See 1 more Smart Citation
“…Results showed that adding home NIV to oxygen therapy significantly prolonged the time to readmission or death within 12 months. 267 Two previous retrospective studies 268,269 and two of three RCTs 267,270-273 reported reductions in re-hospitalization and improved survival with using NPPV post-hospitalization. Two studies reported decreases in mortality and hospitalization rates while another showed no benefit of NPPV for survival.…”
Section: Ventilatory Supportmentioning
confidence: 97%
“…267 Patients with body mass index >35 Kg/m 2 , obstructive sleep apnea syndrome, or other causes of respiratory failure were excluded. Of 2,021 patients screened, only 124 (6%) were eligible.…”
Section: Ventilatory Supportmentioning
confidence: 99%
“…In COPD, persisting chronic respiratory failure should be demonstrated after an acute exacerbation before initiating long-term HMV [2]. Prognosis of patients with persisting hypercapnic respiratory failure after an acute exacerbation is poor compared to patients with transient hypercapnia or eucapnia [4, 5].…”
Section: Phases Of Mechanical Ventilation From Initiation To Long-termentioning
confidence: 99%
“…Previous studies have shown that the longer term prognosis in patients who have had an AECOPD requiring NIV is poor 24,25,34 . These patients may also be frequently readmitted to hospital 21,34,35 , though this can be reduced by the provision of domiciliary NIV 36 . There is a danger that patients spend their last few months of life lurching from one crisis to another with much of their time spent in hospital with life of marginal quality.…”
Section: Ventilatory Failure Developing or Worsening After Admissionmentioning
confidence: 99%